The Identification of Vocabulary Learning Strategies of Male and Female Students - Febrina, Mauizotul; Azhar, Fadly; Purwanti, Indah Tri (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
The research aims to find out vocabulary learning strategies used by male and female students. It uses quantitative methods. The research population involved second-grade students at MTs Darul Hikmah Pekanbaru. The research sample was 100 students. The researchers used questionnaires to collect data on vocabulary learning strategies. There were 34 items with 5 strategies. The result of the data showed that male and female students employed more than one strategy in learning vocabulary. Those strategies were determination, social, memory, cognitive, and meta-cognitive strategies. There are differences between male and female students using vocabulary learning strategies. The most common strategy used by male students was cognitive strategy. While, the most common strategy used by female students were cognitive, memory, determination, and meta-cognitive strategy.